Constraints on the K0S→μ+μ− Branching Fraction; Physical Review Letters; Vol. 125, iss. 23 - Aaij R. Roel; Beteta C. A. Carlos Abellan; Ackernley T.; Adeva B. Bernardo; Eydelman S. I. Semen Isaakovich; Kharisova A. E. Anastasiya Evgenjevna; Panshin G. L. Gennady Leonidovich (2020, 2020)
Title screen